2017
DOI: 10.1111/jfpe.12616
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimum vapor bleeding arrangements for sugar juice evaporation process

Abstract: The sugar juice evaporation process consists of juice heater, evaporator, and crystallizer. The juice heater increases the temperature of diluted sugar juice from the ambient temperature to the boiling point. The evaporator removes most water content of diluted sugar juice. The crystallizer removes the remaining water content, yielding raw sugar as the final product. Since both the juice heater and the crystallizer require vapor bled from the evaporator, there are interactions between the three components. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Steam consumption by a multiple-effect evaporator can also be minimized by distributing heating surface areas optimally in the process. Previous investigations by Chantasiriwan [6][7][8][9] have demonstrated the existence of the optimum distribution of heating surface areas that results in the minimum steam consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Steam consumption by a multiple-effect evaporator can also be minimized by distributing heating surface areas optimally in the process. Previous investigations by Chantasiriwan [6][7][8][9] have demonstrated the existence of the optimum distribution of heating surface areas that results in the minimum steam consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical vapor compression [7] and thermal vapor compression [8] have been suggested as methods to increase the energy efficiency of the multiple-effect evaporator. The energy efficiency of the multiple-effect evaporator can also be increased by the optimum distribution of heating surface areas [9][10][11][12]. Recently, Chantasiriwan has shown that the energy efficiency of the cogeneration system, in which the evaporation process is a component, can be increased by replacing the forward-feed evaporator with the backward-feed evaporator [13].…”
Section: Introductionmentioning
confidence: 99%
“…A more realistic model by Chantasiriwan () yields a similar conclusion that there exists the optimum distribution of evaporator surface area. For a specified distribution of evaporator surface area, it has also been shown that the minimum steam consumption occurs at the optimum distribution of juice heater surface area (Chantasiriwan, ). The previous works suggest that further reduction in steam consumption may be attained by simultaneously optimizing the distributions of evaporator and juice heater surface areas.…”
Section: Introductionmentioning
confidence: 99%
“…This article is an extension to the previous investigation by Chantasiriwan (2018), which is concerned with the optimum distribution of juice heater surface area in the sugar evaporation system with the quintuple-effect evaporator. It was shown that, for a specified distribution of evaporator surface area, there exist two different optimum distributions of a fixed surface area of juice heater corresponding to the maximum sugar juice flow rate and the minimum steam consumption.…”
Section: Introductionmentioning
confidence: 99%